Perception of Elementary School teachers and 8th Grade Students regarding English as a Medium of Instruction at Elementary Level - Naz, Samina; Raheem, Muhammad Arslan; Usman, Aqsa (Pakistan Languages and Humanities Review, 2025)
The current study is focused on finding out how 8th grade students and teachers regard the use of English as the language of instruction (EMI) in elementary schools. The objective behind this study is to inquire into the conceit of teachers and students of 8th grade regarding EMI at the elementary school level, as well as to evaluate EMI’s effect on what students learn and investigating how teachers and students in D. G. Khan district, Pakistan feel about using English as the main language of study. This study targets 501 elementary-level students of 8th grade and 617 elementary school teachers teaching in 38 elementary schools situated in district D.G. Khan. Out of convenience, the participants in this study group were selected as 224 students and 85 teachers. Separate questionnaires were designed for each group respectively. It was found that both teachers and students like using English as the main language for learning at elementary school. Basing its recommendations on findings and conclusions, this study advises all Punjab schools to switch to using English as the main language for teaching due to globally accepted language and provision of government-supported teachers’ training programs to teach effectively in English medium classrooms. This study also suggests that EMI have positive impacts on students’ learning and both teachers and students are willing for its implementation at elementary level.